Synthesis and biological assay of new 2'-deoxyuridine dimers containing a 1, 2, 3-triazole linker. Part I. (4th March 2019) - Michalska, Lucyna; Wawrzyniak, Dariusz; Szymańska-Michalak, Agnieszka; Barciszewski, Jan; Boryski, Jerzy; Baraniak, Dagmara
Abstract: We describe a simple method for the synthesis of modified dinucleosides containing pyrimidine nucleoside analogues (2'-deoxyuridine, thymidine and 5-fluoro-2'-deoxyuridine). Six different dimers with a 1, 2, 3-triazole linkage were obtained by azide–alkyne 1, 3-dipolar cycloaddition (click reaction), starting from propargylated 2'-deoxyuridine and 5'-azido-nucleoside derivatives. Their cytotoxic activity was tested in five human cancer cell lines: cervical (HeLa), high grade gliomas (U-118 MG, U-87 MG, T98G), liver (HepG2), and normal human fibroblast cell line (MRC-5) using the sulforhodamine B (SRB) assay. The experiment showed that the obtained dimers with a 1, 2, 3-triazole moiety were very stable compounds, also in the physiological-like media, and had no anticancer activity.